Payment Arrears in the Gas and Electric Power Sectors of the Russian Federation and Ukraine - Gurgen, Emine (IMF Working Papers; Working Paper, 1997)
This paper discusses payments arrears in the Russian Federation and Ukraine, with emphasis on the gas and electric power sectors. Payments arrears, which were triggered primarily by the dislocations experienced during the transition from a centrally planned to a market economy, have reached significant proportions in these two countries. Governments have aggravated the problem by not honoring their own bills and by condoning payments arrears outside the budget. The paper argues that the solution to the problem lies in the implementation of comprehensive systemic reforms and outlines possible measures.